ENTRE CARTAS E CONVERSAÇÕES: ENCONTROS NA DIFERENÇA - Silva, Daiana Pilar Andrade de Freitas (2020)
This essay is an offshoot of a thesis produced in a Brazilian public university. It is a cartographic exercise, which in the process was gaining essay form. A work in which we seek to problematize the effects of encounters between a teacher and children with blindness, understanding that research and writing do not separate: therefore a writtenresearch. We question not only the narrative of the effects produced in the encounters, but also the ways in which the dominant and dominant policies of narrativity impose certain forms of research and writing and exclude others, forms that mostly limit educating to one process that is much more between equals than being a relationship that has the potential for difference. Thus, we seek to think of the thesis produced as an experience in difference, in which other ways of narrating are necessary to make explicit the encounter between us.